Changes in value system and life aspirations of youth in Poland from the perspective of thirty years (1989-2019) - Mirosława Jaworowska (Journal of Modern Science)
Objectives The aim of the analysis of the research results was to find out about changes in the system of values and life aspirations of the young generation of Poles from the perspective of the thirty years (1989-2019). The research was conducted in 1989, 1995, 2000 and 2019 was carried out based on comparative analyses, using a uniform research tool in all four research periods.